2011
DOI: 10.1097/scs.0b013e31822e5edb
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Related Factors of Blood Loss and Blood Ingredients Among Patients Under Hypotensive Anesthesia in Orthognathic Surgery

Abstract: No significant factor was associated with blood loss and reduced blood ingredients among patients in orthognathic surgery with hypotenstive anesthesia. Improvements in anesthesia provided surgeons with more time to promote hemostasis during surgery. Hypotensive anesthesia was a well-accepted method to reduce blood loss during orthognathic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
10
2
Order By: Relevance
“…Administration of vasoconstrictors like adrenaline or a beta-blocker to the nasal passages, reverse Trendelenburg position, controlled hypotension or steroid therapy were suggested (6). Controlled hypotensive anesthesia is commonly used in several surgical interventions using different techniques (7,8). Volatile anesthetics, sympathetic antagonists, β adrenoreceptor antagonists, calcium channel blockers, opioids, and direct-acting vasodilators have been used to achieve controlled hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of vasoconstrictors like adrenaline or a beta-blocker to the nasal passages, reverse Trendelenburg position, controlled hypotension or steroid therapy were suggested (6). Controlled hypotensive anesthesia is commonly used in several surgical interventions using different techniques (7,8). Volatile anesthetics, sympathetic antagonists, β adrenoreceptor antagonists, calcium channel blockers, opioids, and direct-acting vasodilators have been used to achieve controlled hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…38 Perhaps the most surprising finding was the lack of evidence regarding the effect of HA on IOB, because this is a well-established hemostatic measure in maxillofacial surgery. 18,40 Choi and Samman 41 reached a similar conclusion in a review from 2008, remarking that HA might prove significant in OS procedures with anticipated high IOB.…”
Section: Discussionmentioning
confidence: 50%
“…In that respect, we found that in 22 out of 51 papers, the method of measuring estimated blood loss was missing . In 18 out of 51 papers, the estimated blood loss was measured by deducting the volume of saline used from the total volume in the suction unit and by weighing the sponges [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], others 10 mL [43]. In 6 out of 51 papers, losses in sponges were not included Table 1.…”
Section: Measurement Of Blood Lossmentioning
confidence: 99%
“…In bimaxillary surgery, Böttger [6] indeed found a linear correlation between calculated blood loss and operation time, but this correlation was weak for 82 bimaxillary procedures: Spearman correlation coefficient r = 0.325. Chen et al [31] found a weak Spearman rank correlation between operation time and blood loss in 30 mandibular surgery patients (IVRO set-back and genioplasty). Rummasak et al [43], in a retrospective review of 208 patients with bimaxillary orthognathic surgery, reported the following correlation between blood loss and operative time: blood loss = (2.64 * operative time) + 82.…”
Section: Duration Of Surgery and Blood Lossmentioning
confidence: 99%